Maturity assessment of Systems Engineering reusable assets to facilitate MBSE adoption. Issue 1 (2021) - Wu, Quentin; Gouyon, David; Levrat, Eric
Abstract: To enable the transition towards Model-Based Systems Engineering, it is necessary to provide engineering assets models during system architecture design phases. As promoted in the software community, systematic reuse allows significant gains in development productivity and quality. Thus, to develop a reuse strategy, a maturity scale facilitates determining the maturity level at which a company operates. In this way, it is possible to assess the progress margins and therefore estimate necessary efforts to improve maturity through a corresponding action plan. For this reason, this article proposes a scale to evaluate the maturity of the Systems Engineering assets reuse process.